2016
DOI: 10.1371/journal.pone.0147213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assortment of Lens Species with Different Adaptations to Drought Conditions Using SSR Markers

Abstract: The success of drought tolerance breeding programs can be enhanced through molecular assortment of germplasm. This study was designed to characterize molecular diversity within and between Lens species with different adaptations to drought stress conditions using SSR markers. Drought stress was applied at seedling stage to study the effects on morpho-physiological traits under controlled condition, where tolerant cultivars and wilds showed 12.8–27.6% and 9.5–23.2% reduction in seed yield per plant respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…This suggested that grouping of wild accessions was on the basis of Al resistance reactions, while cultigens showed lesser Al tolerance grouping pattern. Similarly, separation of wild accessions from cultigens in lentil has been reported in some recent studies [ 52 , 12 ]. Further, among 4 resistant wilds, ILWL-3 belongs to spp.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This suggested that grouping of wild accessions was on the basis of Al resistance reactions, while cultigens showed lesser Al tolerance grouping pattern. Similarly, separation of wild accessions from cultigens in lentil has been reported in some recent studies [ 52 , 12 ]. Further, among 4 resistant wilds, ILWL-3 belongs to spp.…”
Section: Discussionmentioning
confidence: 60%
“…These markers have been used in lentil to study diversity in relation to many abiotic stresses like drought, heat etc. and can be successfully utilized for diversity analysis for Al resistance as well [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drought increased H 2 O 2 accumulation and lipid peroxidation in plants while reducing ascorbic acid concentrations. Several studies have shown that drought stress causes an increase in proline which is an important parameter in determining the extent of tolerance to drought (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, when only the important characteristics of morphology and physiological are taken into consideration they showed significant positive correlation with the molecular genetic distances. Positive correlation among datasets between molecular markers and morphophysiological traits were also reported for drought tolerant and sensitive cultivars of lentils (Singh et al 2016) and tall fescue (Sun et al 2015). Therefore, morpho-physiological factors should be considered along with the molecular markers for selection of tea cultivars for improving the drought tolerance in tea.…”
Section: Discussionmentioning
confidence: 83%